Periurethral Enterobacterial Carriage in Pathogenesis of Recurrent Urinary Infection. Issue 5937 (19th October 1974) - Cattell, W. R.; McSherry, M. A.; Northeast, A.; Powell, E.; Brooks, H. J. L.; O'Grady, F.
Abstract : Periurethral carriage rates of enterobacteria have been studied in 20 normal women, 34 patients between episodes of bacteriuria, 34 patients with the "urethral syndrome, " and 15 asymptomatic abacteriuric patients with a previous history of frequency and dysuria. Over a six-week period no difference in the Escherichia coli carriage rate was shown between these four groups. The carriage of all enterobacteria was slightly but significantly (P <0.05) lower in normal women compared with the patient groups but no difference was observed between the latter. There was no difference in the recovery rate and carriage of individual E. coli serotypes between the four groups. It is concluded that the presence of enterobacteria or E. coli on the periurethral area is not the principal determinant factor in the pathogenesis of recurrent urinary tract infection or the urethral syndrome and that definition of carriage status is of little practical value in management.